Solution combustion synthesis of Ni-based hybrid metal oxides for oxygen evolution reaction in alkaline medium - Abu Hatab, Aymen S.; Ahmad, Yahia H.; Abdul Rahman, Mohd B.; Al-Qaradawi, Siham Y. (Royal Society of Chemistry, 2022)
Oxygen evolution reaction (OER) has arisen as an outstanding technology for energy generation, conversion, and storage. Herein, we investigated the synthesis of nickel-based hybrid metal oxides (NixM1−xOy) and their catalytic performance towards OER. NixM1−xOy catalysts were synthesized by solution combustion synthesis (SCS) using the metal nitrates as oxidizer and glycine as fuel. Scanning electron microscope (SEM) micrographs display a porous morphology for the hybrid binary NixM1−xOy, the common feature of combusted materials. X-ray diffraction (XRD) of NixM1−xOy depicted well-defined diffraction peaks, which confirms the crystalline nature of synthesized catalysts. The particle size of as-synthesized materials ranges between 20 and 30 nm with a mesoporous nature as revealed by N2-physisorption. The electrocatalytic performance of the as-prepared materials was evaluated towards OER in alkaline medium. Among them, NixCo1−xOy showed the best catalytic performance. For instance, it exhibited the lowest overpotential at a current density of 10 mA cm−2 (404 mV), onset potential (1.605 V), and Tafel slope (52.7 mV dec−1). The enhanced electrocatalytic performance of NixCo1−xOy was attributed to the synergism between cobalt and nickel and the alteration of the electronic structure of nickel. Also, NixCo1−xOy afforded the highest Ni3+/Ni2+ when compared to other electrocatalysts. This leads to higher oxidation states of Ni species, which promote and improve the electrocatalytic activity.